2005
DOI: 10.1107/s1600536805001157
|View full text |Cite
|
Sign up to set email alerts
|

CsYbSe2

Abstract: Caesium ytterbium diselenide, CsYbSe2, crystallizes in space group P63/mmc of the hexagonal system. It is isostructural with CsPrS2, which has the β‐RbScO2 structure type. In the asymmetric unit, the site symmetries of atoms Cs, Yb and Se are m2, m and 3m, respectively. The structure comprises layers of edge‐shared YbSe6 octahedra perpendicular to [001], with Cs atoms between the layers in a trigonal‐prismatic arrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…So far, only the structure of CsYbSe 2 was reported, which was synthesized via complex multiple steps. 43 In this work, we employed a new and simple flux method to grow large single crystals of 112-class compounds, enabling anisotropic physical property measurements and inelastic neutron scattering experiments. In addition, for the first time, we confirmed that new compounds in this CsRESe 2 series crystallize in either trigonal or hexagonal crystal systems, depending upon the size of the RE 3+ ion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, only the structure of CsYbSe 2 was reported, which was synthesized via complex multiple steps. 43 In this work, we employed a new and simple flux method to grow large single crystals of 112-class compounds, enabling anisotropic physical property measurements and inelastic neutron scattering experiments. In addition, for the first time, we confirmed that new compounds in this CsRESe 2 series crystallize in either trigonal or hexagonal crystal systems, depending upon the size of the RE 3+ ion.…”
mentioning
confidence: 99%
“…These can be well-exemplified by the Cs RE Se 2 family. So far, only the structure of CsYbSe 2 was reported, which was synthesized via complex multiple steps . In this work, we employed a new and simple flux method to grow large single crystals of 112-class compounds, enabling anisotropic physical property measurements and inelastic neutron scattering experiments.…”
mentioning
confidence: 99%
“…The rapid change in the E 2g Raman mode energy at 90 K and the associated overlap of this mode with the CEF1 mode from 100 to 200 K is noteworthy. In CsYbSe 2 , there is some evidence for anisotropic negative thermal expansion in these temperature ranges 33,55 . In general, a nearly discontinuous change with temperature of any spectral parameter (such as the energy of the E 2g mode) is suggestive of a phase transition, though we find no direct evidence of any phase transition here.…”
Section: Resultsmentioning
confidence: 99%